The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12681/mms.20229
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary inventory of alien and cryptogenic species in Monastir Bay, Tunisia: spatial distribution, introduction trends and pathways

Abstract: The Mediterranean Sea is a marine biodiversity hotspot under threat. One of the major impacts on its biological resources and services comes from the invasiveness of non-indigenous species (NIS). Nevertheless, NIS monitoring programs in the south basin of the Mediterranean Sea are in an early implementation stage. This study aims to describe NIS and cryptogenic species distribution in Monastir Bay (Tunisia) and to identify risk areas for the introduction and spread of invasive species, providing a baseline for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…In the Aegean Sea, Bariche et al (2020) reported for the first time a non-indigenous nudibranch, using Autonomous Reef Monitoring Structures (ARMS) protocol, proposed by Obst et al (2020). In the Southern Mediterranean Sea, Chebaane et al (2019) sampled through RAS fishing ports and marinas in Monastir Bay, Tunisia. Lastly, the broadest investigation of non-indigenous invertebrates in Mediterranean marinas was conducted by Ulman et al (2017) with both modified RAS and scrapes by hand-held rigid net.…”
Section: Introductionmentioning
confidence: 99%
“…In the Aegean Sea, Bariche et al (2020) reported for the first time a non-indigenous nudibranch, using Autonomous Reef Monitoring Structures (ARMS) protocol, proposed by Obst et al (2020). In the Southern Mediterranean Sea, Chebaane et al (2019) sampled through RAS fishing ports and marinas in Monastir Bay, Tunisia. Lastly, the broadest investigation of non-indigenous invertebrates in Mediterranean marinas was conducted by Ulman et al (2017) with both modified RAS and scrapes by hand-held rigid net.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extraction of sulfated polysaccharides from sea hares has thus far received little attention from scientists and researchers working in the area of marine natural products . The sea hare Bursatella leachii is a marine opisthobranch gastropod mollusk belonging to the Aplysiidae family. , It emerged as an invasive species in the Mediterranean Sea in the mid-1900s. ,, …”
Section: Introductionmentioning
confidence: 99%
“…24,25 It emerged as an invasive species in the Mediterranean Sea in the mid-1900s. 24,26,27 Compounds with an anti-HIV activity and antimalarial properties have been isolated from the purple fluid 28 and the internal organs of B. leachii, respectively. 29 economic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Marinas and harbours are considered as hubs for enhanced NIS recruitment, as they are under greater pressure from maritime traffic and human activities than other natural and artificial coastlines [41][42][43]. These can serve as stepping stones for NIS introduction into local natural habitats since they serve as a refuge for arriving NIS [14,44,45].…”
Section: Introductionmentioning
confidence: 99%